Evaluation of Mannheim’s Peritonitis Index in Prediction of Mortality in Patients with Non-traumatic Hollow Viscus Perforation Peritonitis - Shakya, Vikal Chandra; Pangeni, Anang; Karki, Saurav; Sharma, Lokesh Raj (Journal of Nepal Health Research Council, 2021)
Background: Hollow viscus perforation peritonitis is one of the commonest surgical emergencies with high mortality and morbidity. The objective of this study was to evaluate the effectiveness of Mannheim’s peritonitis index in prediction of mortality in these patients.Methods: This is a retrospective, observational cohort study in these patients managed in a single-center from January 1, 2013 to December 30, 2019. Total index scores were plotted in the receiver operating characteristic curves to find out the cut-off point. Sensitivity, specificity, relative risk, positive and negative predictive values were calculated. The individual risk factors were analyzed for mortality as well.Results: Case records of 395 cases of non-traumatic hollow viscus perforation peritonitis were available, there were 33 mortalities (8.2%), mean score was 22.96 (+7.6) points (range 10-43 points). The sensitivity and specificity with score cut-off of 25 came to be 75.8% and 56.35%; positive and negative predictive value being 13.7% and 96.2%. Risk of patients for mortality with scores >25 was 3.62 times those with scores <25 for mortality. Mortality rate was 2.4% with scores <21, 8.9% with 21–29 and 20.9% with >29 respectively (p-value <0.05). Univariate analysis showed age >50 years, presence of organ dysfunction, diffuse peritonitis, non-colonic origin and character of exudates were significant factors; multivariate analysis showed only organ failure as significant.Conclusions: Mannheim peritonitis index is very useful in stratification of severity of the disease and prediction of mortality in patients with peritonitis, and should be included in management of all these patients.Keywords: Mannheim’s peritonitis index; perforation peritonitis